2015
DOI: 10.18632/oncotarget.4057
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated long non-coding RNA AFAP1-AS1 expression is associated with progression and poor prognosis of nasopharyngeal carcinoma

Abstract: Altered expression of long noncoding RNAs (lncRNAs) associated with human carcinogenesis. We performed a cDNA microarray analysis of lncRNA expression in 12 cases of nasopharyngeal carcinoma (NPC) and 4 non-tumor nasopharyngeal epitheliums. One lncRNA, actin filament associated protein 1 antisense RNA1 (AFAP1-AS1), was identified and selected for further study. AFAP1-AS1 expression was upregulated in NPC and associated with NPC metastasis and poor prognosis. In vitro experiments demonstrated that AFAP1-AS1 kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
183
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(192 citation statements)
references
References 46 publications
8
183
0
1
Order By: Relevance
“…Knockdown of HNF1A-AS suppressed proliferation and migration of NPC cells [100]. AFAP1-AS1 knockdown increased AFAP1 protein expression, thereby inhibiting the NPC cell migration and invasive capability [101]. Recently, high-through put analysis revealed that lncRNA LOC100129148 was highly expressed in NPC.…”
Section: Oncogenic Lncrnasmentioning
confidence: 99%
“…Knockdown of HNF1A-AS suppressed proliferation and migration of NPC cells [100]. AFAP1-AS1 knockdown increased AFAP1 protein expression, thereby inhibiting the NPC cell migration and invasive capability [101]. Recently, high-through put analysis revealed that lncRNA LOC100129148 was highly expressed in NPC.…”
Section: Oncogenic Lncrnasmentioning
confidence: 99%
“…30,35,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] In this review, the related clinicopathological characteristics and molecular functions of this lncRNA in cancers are presented in Tables 1 and 2.…”
Section: Identification Of Afap1-as1mentioning
confidence: 99%
“…Recent studies have shown that AFAP1-AS1 promoted cells proliferation and invasion in nasopharyngeal carcinoma, hepatocellular carcinoma, esophageal squamous cell carcinoma, gallbladder cancer [17, 19, 22, 23]. To investigate roles played by AFAP1-AS1 in CCA, we first examined the expression of AFAP1-AS1 in all 4 CCA cell lines (QBC939, CCLP1, HuCC-T1 and RBE) and the nonmalignant cholangiocyte cell line BEC.…”
Section: Resultsmentioning
confidence: 99%
“…LncRNA CPS1-IT1 was observed to be upregulated in intrahepatic cholangiocarcinoma and knockdown of CPS1 CPS1-IT1 decreased the proliferation and indued the apoptosis of ICC-9810 cells [16]. LncRNA AFAP1-AS1 (actin filament associated protein 1 antisense RNA1), has been reported to be upregulated in esophageal adenocarcinoma, hepatocellular carcinoma, pancreatic ductal adenocarcinoma, and nasopharyngeal carcinoma [17-20]. However, the expression and detailed function of AFAP1-AS1 in CCA remains largely unclear and needs to be investigated.…”
Section: Introductionmentioning
confidence: 99%